Stay with Me: Factors Influencing Teacher’s Retention in Private Elementary Schools - Sumipo, Jasmin (Advances in Social Sciences Research Journal, 2020)
This research study sought to find out the factors which influence teachers’ decision to stay among the selected private elementary schools in Tubigon, Bohol. A researcher -made questionnaire based on Fredrick Herzberg’s Motivation- Hygiene Theory supplemented with informal interviews were used to gather the perceptions of the research participants. This quantitative-qualitative study used purposive sampling to determine the eighteen teacher participants from the three private elementary schools. Using a weighted mean formula to interpret the data, findings revealed that motivational factors on the job are strong influencing factors responsible for teachers’ retention. Despite the low salary they received, the participants chose to stay because they felt satisfied in other areas. Truly, intrinsic motivational factors are stronger forces that instill teachers’ loyalty to the school. This is in congruence with Herzberg Theory which states that the higher the motivational factors, the greater the percentage of worker’s retention.